A Learning Health System Framework to Operationalize Health Data to Improve Quality Care: An Australian Perspective - Enticott, Joanne C.; Melder, Angela; Johnson, Alison; Jones, Angela; Shaw, Tim; Keech, Wendy; Buttery, Jim; Teede, Helena (Frontiers in Medicine, 2021)
Our healthcare system faces a burgeoning ageing population, rising complexity and escalating costs. Around 10% of healthcare is harmful, and evidence is slow to implement. Innovation to deliver a quality, sustainable, health system is vital yet methods are challenging. The aim of this paper is to describe the process and present a perspective on a coproduced of a Learning Health System framework. The development of the Framework was led by publicly funded, collaborative, Academic Health Research Translation Centres, with a mandate to integrate research into healthcare to deliver impact. The focus of the framework is “learning together for better health” with coproduction involving leadership by an expert panel, a systematic review, qualitative research, a stakeholder workshop and iterative online feedback. The co-produced Framework incorporates evidence from stakeholders, from research from data (practice to data and data to new knowledge) and from implementation top take new knowledge to practice. This continuous learning approach, aims to deliver evidence-based healthcare improvement and is currently being implemented and evaluated.